Parameter Justification of a Signal Recognition Algorithm Based on Detection at Two Intermediate Frequencies - Tran Huu Nghi; A. S. Podstrigaev; Nguyen Trong Nhan; D. A. Ikonenko (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The signal recognition task for the purposes of RF spectrum management can be solved using a signal recognition algorithm with detection at two intermediate frequencies. This algorithm is based on time–frequency analysis using fast Fourier transform (FFT) and signal envelope processing. Due to the relative simplicity of transformations, this algorithm is implemented on commercially available field programmable gate arrays and allows processing received signals in near real-time. However, the justification of the algorithm parameters providing effective signal recognition by the criterion of minimizing the signal-to-noise ratio (SNR) has not performed so far.   Aim. Justification of parameters of the developed signal recognition algorithm, providing the minimum required SNR at the algorithm input.   Materials and methods. The efficiency of the developed algorithm was estimated by computer simulation in the MATLAB environment.   Results. The influence of the parameters of functional blocks and received signals on the efficiency of the developed algorithm was investigated. For chirp, simple pulse, binary, and quadrature phase shift keying signals, the following parameters are recommended: a pulse duration of 5…20 μs; a chirp rate of 0.8…24 MHz/μs; a code duration of 0.5…1 μs. For these signal parameters, the parameters of the algorithm ensuring its efficiency according to the given criterion are as follows: the number of FFT points equals 1024; the Hamming weight window; bandwidths of band-pass filters are 4 MHz; signal envelope amplitude averaging coefficient equals 0.15…0.25.   Conclusion. The algorithm with the scientifically valid parameters can be used for recognition of signals at the input minimum SNR for the given types and parameters of signals.